2023
DOI: 10.3390/pharmaceutics15112633
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Core–Shell Electrosprayed Microcapsules for Enhanced Oxidative Stability of Vitamin A Palmitate

Elnaz Z. Fallahasghari,
Marie Højgaard Lynge,
Emma Espholin Gudnason
et al.

Abstract: Vitamin A is an essential micronutrient that is readily oxidized. In this study, the encapsulation of vitamin A palmitate (AP) within a core–shell carbohydrate matrix by co-axial electrospray and its oxidative stability was evaluated. The electrosprayed core–shell microcapsules consisted of a shell of octenyl succinic anhydride (OSA) modified corn starch, maltose (Hi-Cap), and a core of ethyl cellulose–AP (average diameter of about 3.7 µm). The effect of different compounds (digestion-resistant maltodextrin, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…It was also suggested that the monoaxially produced microcapsules showed the highest oxidation due to their emulsification steps and a longer processing time [ 32 ]. Moreover, in our previous study, core–shell electrosprayed microcapsules of ethyl cellulose-Hi–Cap also showed an enhanced oxidative stability of the lipophilic vitamin A palmitate, mainly due to the absence of the bioactive compound on the surface of the microcapsules, as observed by DSC- isothermal analysis [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was also suggested that the monoaxially produced microcapsules showed the highest oxidation due to their emulsification steps and a longer processing time [ 32 ]. Moreover, in our previous study, core–shell electrosprayed microcapsules of ethyl cellulose-Hi–Cap also showed an enhanced oxidative stability of the lipophilic vitamin A palmitate, mainly due to the absence of the bioactive compound on the surface of the microcapsules, as observed by DSC- isothermal analysis [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The oxidative stability of encapsulated CLO was evaluated in an oxygen atmosphere by the DSC isothermal method, using the DSC 250 (TA instrument Ltd., New Castle, UK) oxidation induction time (OIT) method described by Fallahasghari et al [ 33 ]. The DSC was calibrated with high-purity indium standard.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have been conducted to investigate techniques for the preparation of core–shell drug particles to improve drug administration. Engineering the surface properties to develop micronized particles with a core–shell structure [ 8 , 9 , 10 ] or to achieve particle agglomeration with cohesive force to realize the efficient aerosolization and flowability are effective approaches in drug delivery [ 11 ]. The core–shell-structured particles have an optical particle size that is larger than the aerodynamic particle size of 5 μm, but they exhibit lower inertia due to their lower density, which could contribute to its superior aerodynamics; in comparison, particle agglomeration utilizes the cohesion of fine particles to form an agglomerate, and they deagglomerate into fine particles via collision in the inhaler.…”
Section: Introductionmentioning
confidence: 99%